2022
DOI: 10.1177/13684302221101317
|View full text |Cite
|
Sign up to set email alerts
|

The tethered humanity hypothesis among victims of interpersonal harm: The role of apologies, forgiveness, and the relation between self-, other-, and meta-perceptions of humanity

Abstract: When interpersonal harm is inflicted, victims stop seeing themselves as fully human. The tethered humanity hypothesis proposes that victims restore a full human status when perpetrators undertake attempts at reconciliation and victims manage to reestablish the humanness of their perpetrators. In two studies, we tested this hypothesis and manipulated the perpetrators attempts at apologizing for their misconduct. Participants were either included or socially excluded and received a full or self-exonerating apolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Further, Vaes and Bastian (2021) revealed that the above effect also occurred among self-dehumanized victims. Additionally, self-dehumanized individuals could still increase their humanness through the above approach even without perpetrators’ apology ( Vaes et al, 2022 ). Therefore, the prosociality of self-dehumanized objectification-victims may not decrease if they are offered a chance to forgive their perpetrators who objectified them.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Vaes and Bastian (2021) revealed that the above effect also occurred among self-dehumanized victims. Additionally, self-dehumanized individuals could still increase their humanness through the above approach even without perpetrators’ apology ( Vaes et al, 2022 ). Therefore, the prosociality of self-dehumanized objectification-victims may not decrease if they are offered a chance to forgive their perpetrators who objectified them.…”
Section: Discussionmentioning
confidence: 99%